Reusing Model Transformations across Heterogeneous Metamodels - Wimmer, Manuel; Kusel, Angelika; Retschitzegger, Werner; Schönböck, Johannes; Schwinger, Wieland; Sánchez Cuadrado, Jesús; Guerra, Esther; de Lara, Juan (Electronic Communications of the EASST, 2012)
Model transformations are key enablers for multi-paradigm modeling. However, currently there is little support for reusing transformations in different contexts since they are tightly coupled to the metamodels they are defined upon, and hence reusing them for other metamodels becomes challenging. Inspired from generic programming, we proposed generic model-to-model transformations, which are defined over so-called metamodel concepts, which are later bound to specific metamodels. Nevertheless, the current binding mechanism lacks automated resolution support for recurring structural heterogeneities between metamodels. Therefore, based on a systematic classification of heterogeneities, we propose a flexible binding mechanism being able to automatically resolve recurring structural heterogeneities between metamodels. For this, the binding model is analyzed and required adaptors are automatically added to the transformation.